Impact of ketamine as an adjunct sedative in acute respiratory distress syndrome due to COVID-19 Pneumonia. (November 2021) - Garner, Orlando; Patterson, Jonathan; Mejia, Julieta Muñoz; Anand, Vijay; Deleija, Juan; Nemeh, Christopher; Vallabh, Meghna; Staggers, Kristen A.; Howard, Christopher M.; Treviño, Sergio Enrique; Siddique, Muhammad Asim; Morgan, Christopher K.
Abstract: Purpose: Deep sedation is sometimes needed in acute respiratory distress syndrome. Ketamine is a sedative that has been shown to have analgesic and sedating properties without having a detrimental impact on hemodynamics. This pharmacological profile makes ketamine an attractive sedative, potentially reducing the necessity for other sedatives and vasopressors, but there are no studies evaluating its effect on these medications in patients requiring deep sedation for acute respiratory distress syndrome. Materials and methods: This is a retrospective, observational study in a single center, quaternary care hospital in southeast Texas. We looked at adults with COVID-19 requiring mechanical ventilation from March 2020 to September 2020. Results: We found that patients had less propofol requirements at 72 h after ketamine initiation when compared to 24 h (median 34.2 vs 54.7 mg/kg, p = 0.003). Norepinephrine equivalents were also significantly lower at 48 h than 24 h after ketamine initiation (median 38 vs 62.8 mcg/kg, p = 0.028). There was an increase in hydromorphone infusion rates at all three time points after ketamine was introduced. Conclusions: In this cohort of patients with COVID-19 ARDS who required mechanical ventilation receiving ketamine we found propofol sparing effects and vasopressor requirements were reduced, while opioid infusions were not.